2019
DOI: 10.1155/2019/1536925
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Basalt Fibers on Wind Turbine Blades through Finite Element Analysis

Abstract: Here we use finite element analysis to determine the suitability of basalt fiber as a substitute for E-glass in structural applications, which would improve the cost effectiveness of small wind turbine blades. Five NACA (National Advisory Committee for Aeronautics) profiles were evaluated to select the optimum shape for the wind operation conditions. To obtain the wind load pressure distribution over the blade, a computational aerodynamic analysis by CFD (computational fluid dynamics) was performed based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Based on the von Mises stress formula in CFD simulations, it was found that positive basalt fiber-based compounds for conventional material substitution can reduce deformation by up to 96%. [15] The von Mises stress is a measure of the total overall stress acting on a material including the normal stresses in the x and y directions as well as the shear stresses.…”
Section: P=v×imentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the von Mises stress formula in CFD simulations, it was found that positive basalt fiber-based compounds for conventional material substitution can reduce deformation by up to 96%. [15] The von Mises stress is a measure of the total overall stress acting on a material including the normal stresses in the x and y directions as well as the shear stresses.…”
Section: P=v×imentioning
confidence: 99%
“…Figure 4. Von Mises stress evaluation for E-glass-epoxy and basalt-epoxy at 40 m/s using CFD simulation[15] …”
mentioning
confidence: 99%
“…Fiber-reinforced composites (FRCs) are found to be potential blade materials for SWT applications due to their lightweight and better mechanical properties [5]. E-Glass FRCs are presently used materials for developing SWT blades and carbon, basalt and flax FRCs are proposed as future materials for SWT blades [6,7]. Glass FRCs are cost-competitive materials, however, they are observed to possess moderate tensile and fatigue properties.…”
Section: Introductionmentioning
confidence: 99%
“…Promising future directions for the composite materials are also discussed. V. García et al, [14] studied the suitability of basalt fibers on wind turbine blade applications using computation techniques. He concluded that, composite materials are an excellent replacement for metals in wind turbine applications.…”
Section: Introductionmentioning
confidence: 99%